De Girolamo Fracastoro a Archie Cochrane: da instituição privilegiada à medicina baseada em evidências - Daher, Wilson (2006)
This essay is a historical-review study aiming to revise some reports based on reflexions of authors of the health field in relation to Evidence-Based-Medicine since its beginning until the current tendencies. Despite the great technological and scientific advances nowadays, we have been wondering about if there is some space for medical practice as art connected with science. The research was outlined based in some events and figures from the history of medicine, mainly the ones concerned to Gerolamo Fracastoro,s seminaria prima , Louis Pasteur, s néants and Ignácio Philipe Semmelweis, s dirty hands . Through these, we were able to understand a direction to the scientific knowledge by means of these author,s privileged intuition and others to the highest point; that his, the so-called Evidence-Based-Medicine. Through history, we have been certified that our ancestor from the medical field had coped with precarious science, however using much work and art to fulfil such failure. This should guide to return of an intuitive creativity parallel to the current knowledge available nowadays, therefore, the Evidence-Based-Medicine can be the great further advances for clinical activities